1989
DOI: 10.1136/gut.30.8.1099
|View full text |Cite
|
Sign up to set email alerts
|

Food intolerance and the irritable bowel syndrome.

Abstract: SUMMARY Two hundred patients (156 women) with the irritable bowel syndrome were treated with dietary exclusion for three weeks. Of the 189 who completed this study, 91 (48.2%) showed symptomatic improvement. Subsequent challenge with individual foods showed that 73 of these 91 responders were able to identify one or more food intolerances and 72 remained well on a modified diet during the follow up period (mean (SD), 14.7 (7.98) months). Of the 98 patients who showed no symptomatic improvement after three week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
3
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(160 citation statements)
references
References 22 publications
1
148
3
7
Order By: Relevance
“…The prevalence of perceived food intolerance in subjects with IBS in the population seems to be as high as the rates reported in studies in primary and secondary care, where 20-65% attribute their symptoms to adverse food reactions (Simren et al, 2001b;Zar et al, 2001). Milk seems to be the food item most frequently associated with the symptoms (Nanda et al, 1989;Simren et al, 2001b). Wheat and eggs are other products often associated with symptoms in other trials, whereas vegetables, coffee and chocolate were more frequently reported in this study.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The prevalence of perceived food intolerance in subjects with IBS in the population seems to be as high as the rates reported in studies in primary and secondary care, where 20-65% attribute their symptoms to adverse food reactions (Simren et al, 2001b;Zar et al, 2001). Milk seems to be the food item most frequently associated with the symptoms (Nanda et al, 1989;Simren et al, 2001b). Wheat and eggs are other products often associated with symptoms in other trials, whereas vegetables, coffee and chocolate were more frequently reported in this study.…”
Section: Discussioncontrasting
confidence: 48%
“…It has been linked up with immunological, allergic, toxic and psychiatric mechanisms, but the etiology is poorly understood (Rix et al, 1984;Nanda et al, 1989;Zar et al, 2001;Barbara et al, 2002;Isolauri et al, 2004). Musculoskeletal pain and psychiatric disorders are also common in these subjects .…”
Section: Introductionmentioning
confidence: 99%
“…Food exclusion diets require strict adherence, changing eating patterns, selfdiscipline, will-power, and motivation, but the reported high compliance to the diet (>95% average compliance) in our study demonstrates their feasibility. Our high compliance rate may have been due to test results guiding the food elimination diet [28], instead of trial and error, and/ or immediate positive response as seen in self-reported QoL. Therefore, IgE and IgG food testing can help direct the food exclusion diet initially; however, the only modality for truly identifying a clinical reaction to foods is through oral food challenge [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Como a frutose é pouco absorvida, grandes quantidades podem exceder a capacidade de absorção do intestino delgado, resultando em flatulência e diarreia (42) . Dietas de exclusão algumas vezes indicam que o trigo e os produtos lácteos provocam diarreia ou distensão e os ajustes dietéticos podem resultar em melhoras a longo prazo (43,44) . 10.…”
Section: Anamneseunclassified